By Land and By Sea - Beal, Amanda (Maine Policy Review, 2011)
This short article discusses the results of the By Land and By Sea project, in which Maine fishermen and farmers came together to discuss common concerns and to forge new solutions aimed at re-envisioning a unified food system.